Thermal and shock metamorphic features and terrestrial weathering in opaque minerals of some Antarctic ordinary chondrites recovered by Italian expeditions to Frontier Mountain - MARAS, Adriana; MACRI', MICHELE (Massimo Frezzotti & Valter Maggi Museo Nazionale dell'Antartide Felice Ippolito Sezione Scienze della Terra, Università di Siena Via del Laterino 8, 53100 Siena Fax +39-0577-233817, Tel. +39-0577-233818, 2003)
We studied opaque phases present in twenty-five H-chondrites, two L-chondrites and two LL-chondrites recovered by Italian Expeditions to Frontier Mountain. Petrologic types varying from 3 to 6 according to Van Schmus & Wood (1967) and shock stages ranging from S1 to S5 according to Stoeffler et al. (1991). Weathering effects in ordinary chondrites were also studied through reflected light microscopy. Shock features in opaque phases were compared to shock effects on silicate minerals. Physical changes in troilite and kamacite, studied in L-group ordinary chondrites, are present also in H-chondrites. Our study completes Bennett & McSween (1996) research and extends their shock classification based on textural and mineralogical variations of the opaque phases to the H group ordinary chondrites.